The moderating role of firm age in the relationship between R&D expenditure and financial performance: Evidence from Chinese and US mining firms - Rafiq, S.; Salim, Ruhul; Smyth, R. (Elsevier BV * North-Holland, 2016)
We examine the impact of Research and Development (R&D) on the profitability and sales of mining firms in China and the United States (US) and the moderating effect of firm age using Coarsened Exact Matching (CEM). For the combined panel of 168 major US and Chinese mining firms, we find that, on average, a firm engaging in R&D activities earns 4% to 11% higher sales and generates 4% to 13% more profits than firms that do not engage in R&D activities. We also show that, in the mining industry, firm age moderates the relationship between R&D activities and financial performance. A comparatively mature R&D active firm earns 4.4% more profit and generates 7.2% more sales than a younger non-innovative firm. The turning point at which R&D activities switch from making a negative, to positive, contribution to profit and sales is 37 years and 22 years, respectively. Our results are consistent with the liability of newness, meaning that firm investment in R&D takes time to have a real impact on bottom line measures of financial performance. We conclude with a discussion of the practical implications of our results for Chinese and US mining firms.